Occurrence of scuticociliatosis in the flounder Paralichthys adspersus caused by Miamiensis avidus, in Peru - Medina, Marco (2016)
The Scuticociliatosis, a disease caused by ciliates from the order Scuticociliatida characterized by their high potential to invade the host, is a serious problem in marine aquaculture. This paper describes scuticociliatosis infection in farmed flounder Paralichthys adspersus. External and internal signs of infection include necrotic areas in the tegument, abundant mucus, swelling of the visceral cavity with ascitic fluid accumulation, necrotic muscle fibers and brain liquefaction, among others. The ciliate parasite was molecularly identified and characterized as M. avidus, using sequences of mitochondrial gene cytochrome oxidase I (COI), and nuclear genes β-tubulin and the region of the small subunit 18S rRNA, showing synonymy with P. dicentrarchi . All lesions were infested by ciliates. Histologically, ciliates are detected in almost all tissues being the brain the organ more parasitized. The infected specimens associated with secondary bacterial infections, predominantly Vibrio alginolyticus, died after a lethargy period.